(untitled) - Phạm, Minh Thảo; Nguyễn, Kim Loan (H., 2017)
Trình bày văn hóa tộc người Anh, ÁO, Do Thái, Nga, Đức...; TM tham khảo tr.582-589
Keywords: Văn hóa -- Nhân học -- Tộc người -- Châu Âu; Văn hóa tộc người -- Châu Âu